تحليل وتقدير دالة استجابة عرض محصول البطاطا في الجزائر باستخدام نموذج Nerlove للفترة 1990 - 2021: Analysis and estimation of the supply response function of the potato crop in Algeria using the Nerlove model for the period 1990-2021 - عبدوس عبد العزيز, (Journal of North African Economies, 2025)
The potato crop is one of the main agricultural crops in Algeria, which knows many fluctuations, whether in production or prices, which prompted to know the most important factors that affect the change in the behavior of the Algerian farmer in allocating areas for potato cultivation. The study aims to estimate and analyze the response to the most important economic variables during the period 1990-2021 by identifying the factors most affecting the cultivated area of the potato crop by estimating the degree of farmers' response and the time period required to achieve this response and the flexibility of supply for each of them. The study concluded that the changes in the cultivated areas of potatoes in the current season are prices, productivity, total consumption and imports, whether of the same crop or competing crops in the previous season.